On the need to recognize the Greeks in Poland as a national minority - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Members of the Greek community living in Poland are making efforts to obtain the status of a national minority. Their ancestors have been present on Polish lands since the Middle Ages. Over the centuries, Greeks played an important role in the development of economic and scientific life of Polish cities. They were co-creators of Polish culture, art, and animators of the development of Orthodox religious life.
Keywords: Greek; national minority; nationality; Orthodoxy